Gentlemen seek harmony but not uniformity: The heterogeneity of entrepreneurial team and organizational resilience - Shan, Tingting; Tian, Xiaoya (Frontiers in Psychology, 2022)
The purpose of this research is to investigate the association of the heterogeneity of entrepreneurial team with organizational Resilience. In an uncertain environment, whether new ventures can form entrepreneurial resilience at the organizational level in adverse events becomes the key to sustainable development. Based on the theory of heterogeneous advantage and identity characteristics, this paper constructed a research framework of “Structure-Behavior-Result” and described the mechanism and boundary conditions of the heterogeneity of entrepreneurial team affecting organizational resilience in detail. The role of Confucian traditional culture as a moderator has also been analyzed. Data has been obtained from 390 entrepreneurs in China. All hypotheses were tested using Mediated model with regulation. It has been found that the heterogeneity of entrepreneurial team has positive effect on organizational Resilience. It has also been discovered that cross-boundary search behavior acted as a partial mediator between the heterogeneity of entrepreneurial team and organizational resilience. The Confucian traditional culture strengthens the relationship between them. The results are helpful in understanding the internal mechanism of the heterogeneity of entrepreneurial team affecting organizational resilience. Theoretical and practical implications have been highlighted and future research suggestions have been provided.